In-Hospital Outcome of Early Versus Late Coronary Intervention in Patients Undergoing Thrombolysis after Acute Myocardial Infarction - Tariq, Muhammad Naeem; Samore, Naseer Ahmed; Rashid, Muhammad Humayoun; Nadeem, Asif; Saif, Mohsin; Jokhio, Abdul Rehman; Azad, Naseem; Noeman, Ahmad; Yamin Bukhar, Syeda Neelam; Chaudhry, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the In-hospital outcome of early versus late coronary intervention in patients undergoing thrombolysis after acute myocardial infarction (STEMI).Study Design: Analytical Cross sectional study.Place and Duration of Study: Department of Cardiology, Punjab Institute of Cardiology, Lahore Pakistan from Jul 2021 to Dec2021.Methodology: Total of (n=100) patients regardless of gender between 30-80 years of age, presented with acute ST-elevated myocardial infarction (STEMI) at emergency room of PIC, Lahore and undergo thrombolysis with a thrombolytic agent after taking the informed consents were selected by a consecutive sampling technique. The demographic information which includes (name, age, gender, H/O diabetes, duration of STEMI) was noted. Then patients were randomly divided in two groups (Group A & B). In Group-A, patients were undergone PCI within 24 hours of thrombolysis. In Group-B, patients were undergone PCI after 24 hours of thrombolysis. Then all patients were followed-up in coronary care units for 07 days. If reinfarction occurs or patient was died during hospital stay, it was recorded. All the information was noted in a preformed structured proforma.Results: Out of 100 patients, 10 % (n=10) were in age group of 30-45 years and 90 % (n=90) were in age group of 46-80 years. The mean age was calculated as 60.16 ± 7.13 years. There were 90 (90 %) males whereas 10 (10 %) were females. The frequency of Re-Infarction in early Intervention group was 2(2%) and in late Intervention group it was 10%. (p